Synthesis of β-ketophosphonates through aerobic copper(II)-mediated phosphorylation of enol acetates - Budnikov, Alexander S.; Krylov, Igor B.; Monin, Fedor K.; Merkulova, Valentina M.; Ilovaisky, Alexey I.; Yan, Liu; Yu, Bing; Terent’ev, Alexander O. (Beilstein Journal of Organic Chemistry, 2025)
Aerobic copper(II)-mediated phosphorylation of enol acetates with H-phosphonates leading to the formation of β-ketophosphonates was discovered. The proposed method is applicable to a wide range of H-phosphonates or phosphine oxides as PH-reagents and enol acetates. Unlike previous reports, which generally employed stoichiometric amounts of oxidants or more expensive transition metal catalysts, the present protocol employs only cheap copper sulfate pentahydrate as a catalyst under mild reaction conditions. The achieved phosphorylation proceeds via the formation of P-centered radicals produced by the oxidation of PH-reagents by copper(II)-containing species. Employing anhydrous CuSO4 instead of the pentahydrate led to a dramatic phosphorylation yield drop from 70 to <5%. It seems that the ligand environment of copper is very important for the effective reaction: other Cu(II) and Cu(I) salts, including halides, nitrate, tetrafluoroborate, or perchlorate, were much less effective or completely inert.
Keywords: C–P coupling; copper; enol acetates; β-ketophosphonates; phosphorylation